Association of Serum Vitamin D with Acute Myocardial Infarction in Young Patients (≤40 Years) - Hosen, ABM Imam; Chowdhury, Abdul Wadud; Sabah, Khondker Md Nurus; Amin, Mohammad Gaffar; Ahmed, Mohsin; Haque, Azizul; Uddin, Mohammed Nizam; Sarker, Biswanath; Rubaiyat, Khandaker Abu; Khuda, Md Noor E; et al. (Bangladesh Heart Journal, 2019)
Background: Coronary heart disease (CHD) is the leading cause of death worldwide, with acute myocardial infarction (AMI) being the most severe manifestation. Recent evidence suggests that vitamin D deficiency (moderate/severe) is an important risk factor for coronary artery disease. Objectives: Considering paucity of the literature focusing young MI, the study was planned to assess the relation of different grades of low serum vitamin D with AMI in young patients admitted in a tertiary care hospital. Methods: This Hospital based case-control study was conducted in the department of cardiology in Dhaka Medical College Hospital (DMCH) over 1-year period. Patients with acute MI in young age (≤40 years) admitted in the CCU of DMCH were approached for inclusion in the study. Total 120 subjects (60 cases and 60 controls) were studied. Patients with acute MI were considered as cases and similar number of age and sex matched apparently healthy individual were included as controls. All study population were subjected to relevant investigations and detailed history along with socio-demographic data were collected. Serum vitamin D levels were categorized as severe vitamin D deficiency as a level <10ng/ml, moderate vitamin D deficiency at a level 10-20 ng/ml, vitamin D insufficiency as 21-29 ng/ml and a level of ≥30ng/ml was considered as normal. Serum 25(OH) vitamin D assay was performed for cases and controls using chemiluminescence immunoassay. Vitamin D status (normal/insufficiency vs moderate/severe deficiency) was studied among cases and controls. All necessary information were recorded in a pretested case record form. Statistical analyses were done by SPSS 22. Results: Mean age of cases and controls were 35.31±4.84 and 33.83±5.11 years respectively. Vitamin D deficiency (moderate/severe) was present in 86.7% cases and 46.7% controls and the difference was statistically significant (P<0.001). Among 60 cases of acute MI, 83% patients had acute ST segment elevated myocardial infarction and 17% patients had acute non-ST segment elevated myocardial infarction. Vitamin D deficient (moderate/severe) subjects were more likely to develop AMI than subjects who had normal/insufficient vitamin D levels in blood (OR 7.42, 95%CI 3.18-18.28, P<0.001). And among all the usual coronary risk factors, vitamin D deficiency (moderate/ severe), Hypertension, Family history of premature CAD and smoking were significantly associated with increased incidence of acute MI (STEMI and NSTEMI) (P value<0.05 in all cases). Conclusion: Vitamin D deficiency (moderate/severe) is associated with increased incidence of acute MI in young age (≤40 years). Bangladesh Heart Journal 2019; 34(2) : 80-85